Wang, C.H., Liu, Z.E., Li, Y. & Wang, X.F. (2018) A new species Rubia urceolata (Rubiaceae: Rubieae) from Shennongjia National Park, central China. Phytotaxa 357 (3): 220–224. - Wang, Chun-Hui; Liu, Zhi-E; Li, Ya; Wang, Xiao-Fan (Phytotaxa, 2018)
N/A